Changing Profile of Herpes Zoster in Nepal: A Hospital-Based Study - BMM Kayastha; Pallem Shrestha; R Shrestha; L Lama (Nepal Journal of Dermatology, Venereology & Leprology)
Keywords: Herpes zoster; Clinico-epidemiological profile; dermatomes